An AlGaN/GaN field effect diode with a high turn‐on voltage controllability. Issue 8 (20th April 2017) - Kato, Naoki; Wakejima, Akio; Osada, Yamato; Kamimura, Ryuichiro; Itoh, Kenji; Egawa, Takashi
Abstract : In this paper, an AlGaN/GaN Field Effect Diode (FED) with high turn‐on voltage ( V ON ) controllability is proposed. The structural feature of a δ‐doped GaN cap, an AlGaN barrier, and a GaN channel (GaN/AlGaN/GaN), and selective dry‐etching of the GaN cap, ensure the precise control of V ON which can be modulated by AlGaN barrier layer thickness. The V ON as low as 0.3 V is obtained at the remained AlGaN thickness of 4‐nm with an extremely low estimated V ON deviation.